Research and experiment of a novel flower transplanting device using hybrid-driven mechanism - Zhao, Xiong; Zhang, Xiaoshu; Wu, Qingpei; Dai, Li; Chen, Jianneng (International Journal of Agricultural and Biological Engineering, 2020)
Aiming at decreasing the component complexity and cost of flower transplanting machine, an integrated transplanting method for picking and planting flower seedlings was proposed, and a hybrid-driven five-bar parallel mechanism was designed. A “beak-shaped” trajectory was designed for integrated transplanting requirements, and meantime, either the posture requirements of transplanting claw were determined. Based on the transplanting trajectory of the mechanism, a corresponding mathematical model for solving the link parameters was established, and then the five-bar mechanism was divided into two bar groups, optimization was conducted in two steps based on genetic algorithm and NSGA-II algorithm. Consequently, the optimal solution of the hybrid-driven five-bar parallel mechanism for flower seedling transplanting was obtained. Compared with similar designs, the trajectory displacement of the proposed mechanism is larger in the condition of smaller link size, which indicates that the mechanism can effectively decrease the machine size. The real-time controllable motor angular acceleration fluctuation is smaller and the commutation times are less, which has the advantage of reducing the difficulty of the mechanism control system. Subsequently, the correctness of the design method is verified by kinematics simulation. Finally, the synchronous linkage motion control methods of the two motors were designed, a transplanting experiment of the prototype was carried out, the picking success rate had reached 90%-93.4% and transplanting success rate was 80.5%-86.9% during experiment, which showed that the integrated operation of picking and planting flower seedlings can be realized by the proposed mechanism.Keywords: hybrid-driven mechanism, mechanism optimization, integrated operation of picking and planting, synchronous linkage motion controlDOI: 10.25165/j.ijabe.20201302.5187Citation: Zhao X, Zhang X S, Wu Q P, Dai L, Chen J N. Research and experiment of a novel flower transplanting device using hybrid-driven mechanism. Int J Agric & Biol Eng, 2020; 13(2): 92–100.